Cloning and Expression of Che a 1, the Major Allergen of Chenopodium album in Escherichia coli - Vahedi, Fatemeh; Sankian, Mojtaba; Moghadam, Malihe; Mohaddesfar, Maryam; Ghobadi, Sirous; Varasteh, Abdol Reza (Applied biochemistry and biotechnology, 2011)
Chenopodium album is a weedy annual plant in the genus Chenopodium . C. album pollen represents a predominant allergen source in Iran. The main C. album pollen allergens have been described as Che a 1, Che a 2, and Che a 3. The aim of this work was to clone the Che a 1 in Escherichia coli to establish a system for overproduction of the recombinant Che a 1 (rChe a 1). In order to clone this allergen, the pollens were subjected to RNA extraction. A full-length fragment encoding Che a 1 was prepared by polymerase chain reaction amplification of the first-strand cDNA synthesized from extracted RNA. Cloning was carried out by inserting the cDNA into the pET21b (+) vector, thereafter the construct was transformed into E. coli Top10 cells and expression of the protein was induced by IPTG. The rChe a 1 was purified using histidine tag in recombinant protein by means of Ni–NTA affinity chromatography. IgE immunoblotting, ELISA, and inhibition ELISA were done to evaluate IgE binding of the purified protein. In conclusion, the cDNA for the major allergen of the C. album pollen, Che a 1, was successfully cloned and rChe a 1 was purified. Inhibition assays demonstrated allergic subjects sera reacted with rChe a 1 similar to natural Che a 1 in crude extract of C. album pollen. This study is the first report of using the E. coli as a prokaryotic system for Che a 1 cloning and production of rChe a 1.